Potential Waste Reduction Through 3R (Reduce, Reuse, and Recycle) in Surabaya City: Focus on East and South Surabaya - Nampira, Anisa Apriliani; Pramestyawati, Talent Nia; Afrianisa, Ro’du Dhuha (Journal of Earth and Marine Technology (JEMT), 2024)
Surabaya, the second largest city in Indonesia, faces significant environmental challenges, particularly waste management. To address this issue, the Surabaya City Government, through the Surabaya City Environmental Service (DLH), has introduced an innovative solution: the waste bank program. This practical work aims to evaluate the potential for waste reduction in East Surabaya and South Surabaya using the 3R (Reduce, Reuse, and Recycle) system facilitated by the waste bank program. The waste bank involves the sorting and collecting of recyclable and reusable waste with economic value. Initially, waste sorting was done at the waste bank, but there has been progress. Now, many customers are sorting their waste by type at home. However, some waste bank administrators still need to sort waste on-site due to some customers' inability to do so. The waste bank program also maintains organized weighing and management procedures. All transactions are meticulously recorded in both cash books and passbooks. The results of this program show that waste reduction in active waste banks in East Surabaya and South Surabaya is 0.088%, while the overall waste reduction managed by the Environmental Service (DLH) is 0.571%. To enhance the effectiveness of the waste bank program, it is essential to conduct awareness campaigns to educate the public on the importance of waste management. Additionally, offering rewards to customers could further motivate them to actively participate in the waste bank program.